The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1007/s10533-005-3655-z
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Fe(III)-reducing Bacteria on Uranium Mobility

Abstract: The ability of specialist prokaryotes to couple the oxidation of organic compounds to the reduction of Fe(III) is widespread in the subsurface. Here microbial Fe(III) reduction can have a great impact on sediment geochemistry, affecting the minerals in the subsurface, the cycling of organic compounds and the mobility of a wide range of toxic metals and radionuclides. The contamination of the environment with radioactive waste is a major concern worldwide, and this review focuses on the mechanisms by which Fe(I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
55
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(57 citation statements)
references
References 153 publications
1
55
0
1
Order By: Relevance
“…Although the mechanisms of U(VI) reduction by Desulfovibrio, Geobacter, and Shewanella species are known (16,18), the mechanisms of uranium reduction by clostridia remain unclear. Our previous study showed that it is an enzymatic process, since it occurred only in the presence of growing or on May 11, 2018 by guest http://aem.asm.org/ resting cells; neither the organic acid metabolites generated, the extracellular components of the culture, nor heat-killed cells could reduce uranium anaerobically (4).…”
Section: Tion Of U(vi) (M Hmentioning
confidence: 99%
“…Although the mechanisms of U(VI) reduction by Desulfovibrio, Geobacter, and Shewanella species are known (16,18), the mechanisms of uranium reduction by clostridia remain unclear. Our previous study showed that it is an enzymatic process, since it occurred only in the presence of growing or on May 11, 2018 by guest http://aem.asm.org/ resting cells; neither the organic acid metabolites generated, the extracellular components of the culture, nor heat-killed cells could reduce uranium anaerobically (4).…”
Section: Tion Of U(vi) (M Hmentioning
confidence: 99%
“…Since they are living organisms they migrate in the subsurface porous medium, being subject to a complex of biological, physical and chemical processes. Those micro-organisms act as pseudo-colloids, since their surfaces are often negatively charged, thus having the ability to bind and carry radionuclides through the subsurface environment (Johnsson et al, 2008;Luk'yanova et al, 2008;Seiler et al, 2011;Singer, Farges & Brown Jr, 2009;Wilkins et al, 2006;2010).…”
Section: Pseudo-colloidsmentioning
confidence: 99%
“…Additionally, reduction of U can also occur biotically through metal-reducing bacterial metabolism in sediment (Lovley et al, 1991). This process has notably been used in recent bioremediation programs of contaminated sites where immobilisation of U in sediments was favoured by organic amendment at the sediment surface (Wall and Krumholz, 2006;Wilkins et al, 2006;Renshaw et al, 2007;Barlett et al, 2012).…”
Section: Introductionmentioning
confidence: 99%